Gender and good governance issues in local government of Bangladesh: a baseline report - Gani, Md. Showkat; Sattar, M. Ghulam (BRAC Research and Evaluation Division (RED), 2020)
The study mainly describes the pre-intervention situation of women leadership capacity in local government system of Bangladesh. Data came from the 16 upazilas (sub-district) of 4 districts in Khulna division, where the Gender and Good Governance Programme was in operation. A total of 434 women union parishad (UP) members were interviewed in February-March 2003. Findings reveal that the typical women UP member is someone who is around 35 years old, has secondary or ssc level education, mainly working as homemakers. Thus, the typical elected women UP member do not have much history of formal involvement in activities pertaining to the public domain. Subsequently, it is thus not surprising that they had weak participation in many public activities, such as, infrastructural development, relief and rehabilitation activities, women and child development, communication and linkage with others. On the other hand, they were very active in setting up hygienic toilet, plantation, arsenic awareness creation, attendance of the social justice, and finally the relationship with elites. However, the weakest involvement of women UP members has been in formal committees through which resources are allocated and decisions are made. The observed significant positive association of involvement in developmental activities of women UP members with their age and economic condition indicates that there may have been inadequate opportunity for young women from poorer background to participate and influence developmental work.